VARIASI SUDUT POTONG DAN KECEPATAN POTONG TERHADAP LAJU PEMAKANAN MATERIAL SCM 440 - Pratama, Arianda; Kurniawan, Zaldy; -, Husman; Wahyudie, Ilham Ary (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2023)
During the workpiece turning process, several factors affect the final workpiece, such as the cutting angle and cutting speed. The purpose of this study was to determine the effect of variations in cutting angle and cutting speed on the material consumption rate of SCM 440. The method used in this study is the Response Surface Methodology (RSM), with a two-parameter design, each of which has three levels for each parameter variation. . The results of data analysis obtained eigen values ​​with different signs (positive and negative) which indicated that the stationary point values ​​were in the form of saddle points with a stationary point values of x1 (cutting angle) of -1.686 and x2 (Vc) of 0.199. From the uncoded process, the optimal value for the MRR factor is obtained, namely the cut angle of 10.64° and Vc of 15.28 m/min. The optimum feed rate for SCM 440 material is obtained at an optimal value of neither minimum nor maximum or a saddle point shape at a cutting angle cut of 10.64° and Vc of 15.28 m/min with an MRR area of ​​300-400 mm3/minute.